Scribal education in the Sargonic period - Kraus, Nicholas ca. 20./21. Jh. (Harvard semitic studies, 2021)
Acknowledgments -- Abbreviations -- List of Illustrations -- 1 Introduction -- 1.1 The Sargonic Period -- 1.2 Previous Research -- 1.3 The Concept of a Curriculum -- 1.4 The Sources -- 2 Writing Technology and Paleography -- 2.1 Tablet Manufacture -- 2.2 The Stylus -- 2.3 Tablet Layout and Organization -- 2.4 Current Research on Sargonic Paleography -- 2.5 Typology of Sargonic Tablets -- 2.6 Contextualizing Paleographic Developments -- 2.7 Tablet Orientation -- 2.8 Summary and Conclusion -- 3 The School Texts -- 3.1 Introduction -- 3.2 Elementary Exercises -- 3.3 Mathematics and Metrology -- 3.4 Model Administration -- 3.5 Literature -- 3.6 Traditional Lexical Lists -- 3.7 An Overview of the Curriculum -- 4 Scribal Education in Context -- 4.1 Introduction -- 4.2 Archaeological Evidence -- 4.3 The Sargonic E₂-dub-ba-a? -- 4.4 Literacy in the Sargonic Period -- 4.5 The Language of Instruction -- 4.6 Conclusion -- 5 After Akkade -- 5.1 The Transmission of Knowledge -- 5.2 Summary and Conclusions -- Appendix: School Tablets -- Bibliography -- Index.